2016
DOI: 10.1021/acsami.6b03648
|View full text |Cite
|
Sign up to set email alerts
|

High Anodic Performance of Co 1,3,5-Benzenetricarboxylate Coordination Polymers for Li-Ion Battery

Abstract: We report the designed synthesis of Co 1,3,5-benzenetricarboxylate coordination polymers (CPs) via a straightforward hydrothermal method, in which three kinds of reaction solvents are selected to form CPs with various morphologies and dimensions. When tested as anode materials in Li-ion battery, the cycling stabilities of the three CoBTC CPs at a current density of 100 mA g(-1) have not evident difference; however, the reversible capacities are widely divergent when the current density is increased to 2 A g(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(106 citation statements)
references
References 64 publications
3
103
0
Order By: Relevance
“…Recently, conjugated carboxylates based MOFs, such as Co-BDC [7,8], Mn-BDC [9], Fe-BDC [10,11], Mn-BTC [12], CoBTC [13], Cu-BTC [14] and Fe-BTC [15], are being employed in LIBs and have attracted tremendous attention for their high performances. Further researches indicate that lithium is inserted into organic moiety in these MOFs and it is deduced that the electron withdrawing effect of the conjugated carboxylates should be the main impetus in storing lithium-ions [12][13][14][15][16][17][18][19]. However, MOFs-based electrodes with other kinds of organic linkers are seldom employed in LIBs for the lack of highly-active lithiation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, conjugated carboxylates based MOFs, such as Co-BDC [7,8], Mn-BDC [9], Fe-BDC [10,11], Mn-BTC [12], CoBTC [13], Cu-BTC [14] and Fe-BTC [15], are being employed in LIBs and have attracted tremendous attention for their high performances. Further researches indicate that lithium is inserted into organic moiety in these MOFs and it is deduced that the electron withdrawing effect of the conjugated carboxylates should be the main impetus in storing lithium-ions [12][13][14][15][16][17][18][19]. However, MOFs-based electrodes with other kinds of organic linkers are seldom employed in LIBs for the lack of highly-active lithiation sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the organometallics post‐synthetic modification led FeBTC to possess new crystal structure with clear lattice fringes of 0.226 and 0.214 nm (Figure 1g,h). By analysis (Figure 2b), a sharp characteristic peak of sample Co(OAc) 2 /FeBTC was similar to the crystal structure of cobalt‐benzenetricarboxylic acid compounds 32. According to the comparison on FTIR results of FeBTC and Co(OAc) 2 /FeBTC (Figure 2c), the typical vibration peaks at 1271 and 1716 cm −1 assigned to CO and CO stretching disappeared, which well demonstrated that the high crystallinity composites with small size was formed due to the strong interaction between cobalt acetate and organic ligands of FeBTC.…”
Section: Resultsmentioning
confidence: 57%
“…Generally, nanostructures with smaller size facilitate the penetration of electrolyte into the electrode, shortening the diffusion path of lithium ions. In addition, it has been demonstrated that the BTC ligands in M‐BTC (M = Cu, Co, Mn) can also contribute to the enhancement of capacities . Therefore, the Cu‐BTC species with moderate content in the composites is beneficial to achieve optimal electrochemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the tunable supramolecular components (inorganic and organic species), MOFs are particularly suitable for the electrochemical application. Recently, several groups reported the effect of carboxylate ligands in M‐BTC materials (M = Cu, Co, Mn) on lithium‐storage performances . The experimental and theoretical results strongly revealed that the high lithium‐storage abilities of M‐BTC materials can be ascribed to the multiple electron redox conversion of both metal ions and BTC ligands, as well as the reversible insertion/desertion of Li + ions into/from the benzene rings of BTC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation